2015
DOI: 10.1002/cjce.22293
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of hydrochars produced by hydrothermal carbonization of oil palm shell

Abstract: In this paper, hydrothermal carbonization (HTC) is applied to oil palm shells to produce a solid fuel known as hydrochar. The effect of reaction temperatures 220–290 °C at reaction time 30 min, and a biomass to water ratio of 0.15 g/g (15 wt %) was investigated for synthesis of hydrochar. The hydrochar yield percentage decreased from 62.4 to 43 % with increasing temperature from 220 to 290 °C. In addition, carbon percentage increased with an increase in temperature from 26.93 (oil palm shell) to 63.77 % (hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 64 publications
(122 reference statements)
4
30
0
Order By: Relevance
“…The peak around 1600 cm -1 attribute to aromatic groups (lignin and aromatic groups) which is formed during carbonization [8]. The intensity around 1000 cm -1 shows CO-bonds whose intensity decrease after carbonization because of several CO-bonds are breakdown [8].…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak around 1600 cm -1 attribute to aromatic groups (lignin and aromatic groups) which is formed during carbonization [8]. The intensity around 1000 cm -1 shows CO-bonds whose intensity decrease after carbonization because of several CO-bonds are breakdown [8].…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%
“…The intensity weakens after the hydrothermal process which indicates that several aliphatic chains are broke down during carbonization process [7]. The peak around 1600 cm -1 attribute to aromatic groups (lignin and aromatic groups) which is formed during carbonization [8]. The intensity around 1000 cm -1 shows CO-bonds whose intensity decrease after carbonization because of several CO-bonds are breakdown [8].…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%
“…Biomass feedstock, in general, has been an interesting candidate for biofuels, but the statistics demonstrated that only 10 % of the global alternative renewable energy is generated from biomass. 1,2 The abundance, sustainability and low cost of biomass wastes have promoted more attention and recognition of these wastes to be a CO2 neutral substitute of fossil fuels, in addition to reducing waste disposal in the environment, such as sulfur and nitrogen emissions. 3,4 Biofuels generally offer many benefits, such as sustainability, greenhouse gas emissions reduction, regional development, especially in poorer regions where families survive from subsistence agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] The hydrothermal process provides a higher yield of product with higher energy efficiency, higher carbon content, more surface chemical groups, and lower ash content compared with solid fuel produced by pyrolysis. 2,12,13 Babassu (Orbignya sp.) is a native palm tree from Brazil and its area of concentration is the state of Maranhão and Piauí (northeastern states of Brazil), with almost 10 million hectares with a very high average density of 200 trees/hectare.…”
Section: Introductionmentioning
confidence: 99%
“…Among different utilization methods of biomasses (Liu and Han 2015;Zhao et al 2016), carbonization processes are beneficial routes that can convert biomass residues to biochar, which is attractive for energy use (Liu and Han 2015;Nizamuddin et al 2015a). Two types of biochar, namely pyrolysis and hydrothermal carbonization (HTC), yield products that are obviously different in characteristics because of differences of thermo-chemical conditions such as temperature and surroundings for HTC and pyrolysis.…”
Section: Introductionmentioning
confidence: 99%